Remote Traumatic Brain Injury Is Associated with Motor Dysfunction in Older Military Veterans. (20th January 2017) - Gardner, Raquel C; Peltz, Carrie B; Kenney, Kimbra; Covinsky, Kenneth E; Diaz-Arrastia, Ramon; Yaffe, Kristine
Abstract: Background: Traumatic brain injury (TBI) has been identified as a risk factor for Parkinson's disease (PD). Motor dysfunction among TBI-exposed elders without PD has not been well characterized. We sought to determine whether remote TBI is a risk factor for motor dysfunction on exam and functionally relevant motor dysfunction in day-to-day life among independently living elders without PD. Methods: This is a cross-sectional cohort study of independently living retired military veterans aged 50 or older with ( n = 78) and without ( n = 85) prior TBI—all without diagnosed PD. To characterize multidimensional aspects of motor function on exam, the Unified Parkinson's Disease Rating Scale (UPDRS) Motor Examination was performed by a board-certified neurologist and used to calculate a modified UPDRS (mUPDRS) global motor score and four domain scores (tremor, rigidity, bradykinesia, and posture/gait). Functionally relevant motor dysfunction was assessed via self-report of falls within the past year. Results: In analyses adjusted for demographics and comorbidities that differed between groups, compared with veterans without TBI, those with moderate-to-severe TBI were more likely to have fallen in past year (33% vs. 14%, risk ratio 2.5 [95% confidence interval 1.1–5.4]), had higher (worse) mUPDRS global motor ( p = .03) and posture/gait scores ( p = .02), but not higher tremor ( p = .70), rigidity ( p = .21), or bradykinesia scores ( p = .22). Mild TBI was not associated with worse motor function. Conclusions: Remote moderate-to-severe TBI is a risk factor for motor dysfunction—defined as recent falls and impaired posture/gait—among older veterans. TBI-exposed older adults may be ideal candidates for aggressive fall-screening and prevention strategies.